Monoclonal antibody against VP0 recognizes a broad range of human parechoviruses - Tripathi Lav; Hietanen Eero; Merilahti Pirjo; Teixido Laura; Sanchez-Alberola Neus; Tauriainen Sisko; Susi Petri (ELSEVIER, 2022)
Parechoviruses (PeVs) are common viruses that cause mild gastrointestinal or respiratory symptoms to severe central nervous system infections. In infants, parechovirus infection is one of the leading causes of lifethreatening viral disease. High-quality antibodies with broad binding specificities are essential to improve accurate parechovirus diagnosis in diagnostic laboratories. Such antibodies have potential in the development of rapid antigen detection assay against PeVs. In the present study, VP4 and VP2 genes from human parechovirus A1 (PeV-A1) were cloned and VP0 fusion protein produced to develop monoclonal antibodies against PeVs. Two pan-parechovirus antibodies, one IgG and one IgM isotype, were isolated. The properties of IgG1/kappa monoclonal (designated as Mab-PAR-1) was studied further. Mab-PAR-1 was shown to be functional in western blot against denatured recombinant protein and viral particles. In immunofluorescence assay, the antibody tested positive for nineteen PeV-A1 isolates while showing no cross-reactivity to fourteen entero- and rhinovirus types. In addition, Mab-PAR-1 showed positive reactivity against five other cultivable parechovirus types 2-6. A unique Mab-PAR-1 epitope located in the junction of the three capsid proteins VP0, VP1, and VP3 was identified using a peptide library screen. This study demonstrates that PeV-A1-VP0 protein is functional antigen for developing monoclonal antibody for diagnosis of broad range of parechovirus infections.